Efectividad de la rehabilitación cardiorrespiratoria en la capacidad ventilatoria de pacientes con lesión medular alta. Una revisión bibliográfica (2019)
OBJECTIVE: Evaluate the effectiveness of ambulatory cardiorespiratory rehabilitation in patients with high spinal cord injury. METHODOLOGY: A search was made in the following databases: SCiensetDirect, Scopus and Google Scholar. In this way one of the selected studies was identified from the bibliographic reference of another previously selected article. Initially, a series of articles related to the research were selected from their titles and abstracts reviewed by the researcher in charge. Those studies that were not useful for the investigation were immediately excluded; the articles that had high relation with the subject to study were analyzed completely. RESULTS: During the investigation it was found that the articles selected for the achievement of the research objective had positive changes in the quality of life and cardiorespiratory functioning in all the participants. And also that the population under study in each article were mostly small populations with minimum amounts of 6 and maximum of 60. CONCLUSION: This literature review allows us to conclude that patients with spinal cord injury can improve their respiratory capacity, contributing to their quality of life, since the studies found allow the 100% effectiveness of cardiorespiratory rehabilitation. nevertheless, more research is required in this area to strengthen knowledge and promote adequate interv